Simulasi Pembebanan Gaya Angin pada Baliho Berdasarkan Kode Pembebanan Peraturan Muatan Indonesia dan British Standard BS6399 - Arie Febry Fardheny (Universitas Lambung Mangkurat, 2007)
This simulation show 2 major problems, first about wind force in Indonesia loading code, 1970 which is older and no revision. Second, about signboard design for wind force in Indonesia loading code and British loading code, which is British code using envirotment, location and elevation for wind force. Model Simulation are one leg signboard (baliho type) and two leg signboard. This simulation using finite element software. Result show a lower wind force than British code, which might to consider a revision for Indonesia wind force code. Another result show that deflection in one leg signboard is large if there always a maximum than code . This is a reason why two leg is now use in Banjarmasin.